Preparation and characterization of polymeric micelles for disinfectant coating of Catheters - Hathaichanok Pheungkham (2018)
The disinfectant loaded micelle fabrication were investigated as a carrier for 2-benzyl-4-chlorophenol (OBPCP), a disinfectant agent. Micelles were assessed in terms of the drug entrapment efficiency by suitable fabrication process. Results showed that a film sonication method provided the highest drug loading density at 16.35 ± 0.52%. To utilize numerous advantages of these polymer micelles, micelles containing OBPCP were coated on the surface of catheters using Layer-bylayer (LbL) dip coating technique, highlighting the protocol as an improvement in the prolong release of the drug from a period of several hours to several weeks.